Utilizing microsoft excel spreadsheet technology to improve senior secondary school students’ achievement and retention in quadratic function in Nigeria education - Iji, Clement Onwu; Abakpa, Benjamin Ogbole; Agbo-Egwu, Abel Okoh; Takor, David Iortuhwa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study examined effect of Ms-Excel spreadsheet technology on senior secondary two students’ achievement and retention in quadratic function graphs in Education Zone C Benue State, Nigeria. The study employed a quasi-experimental, non-randomized pre-test post-test control group design. A sample of 302 SS 2 students from two schools in Benue education zone C were selected from a population of 10,918 SS 2 students for the study using purposive sampling technique. Data were collected using Quadratic Function Achievement Test (QFAT) and Quadratic Function Retention Test (QFRT) instruments. The instruments were validated by five experts, two in Mathematics Education, one in Measurement and Evaluation and two Mathematics teachers. The reliability of QFAT was 0.82. Research questions were answered using mean, standard deviations and percentages (scatter gram) while hypotheses were tested using Analysis of Covariance (ANCOVA) at 0.05 level of significance. The results of the study showed among others, that SS2 students taught quadratic function graphs using Ms-Excel spreadsheet technology improved more on their achievement and retention with no gender difference. Among suggestions made were, the need to create awareness among Mathematics teachers, Mathematics educators and curriculum planners to integrate Ms-Excel spreadsheet in particular and ICT in general as a teaching strategy in Mathematics teaching and learning process.